Looking for Melayu: Translators and Seafarers - Villareal, Corazon D. (Archīum Ateneo, 2024)
This essay explores literary relations between the Philippines and Malaysia through a study of translational exchange between the two countries. It argues that translational exchange between the Philippines and Malaysia cannot be understood only through a study of contemporary translations since the connections between the two countries date back to pre-colonial times. Other than a discussion of some contemporary translations, the article cites two cases of translational exchange. The first is Pigafetta’s account of Enrique, the Malay slave/translator who accompanied Magellan in his expedition to the Philippines, and the appropriation of this account by a Malaysian historical novelist. The other case is the translations of Badjau-Sama tales. The link to the shared past between the Philippines and Malaysia in pre-modern times is Melayu, a cultural complex that can be understood partly through a study of common stories and tales that have that have undulated in the borderless seas of south of the Philippines and Sabah. We cannot just translate Malaysia as if it were apart from or foreign to us since there are components in our culture that connect inextricably with Melayu. In a sense, we translate Malaysia as we translate ourselves.